Public participation in landscape planning: Effective methods for implementing the European Landscape Convention in Norway. (March 2015) - Eiter, Sebastian; Vik, Marte Lange
Highlights: We evaluate public participation in spatial planning according to five criteria. We identify ten public participation methods as being particularly effective. To increase scores for all criteria, it is necessary to employ different methods. Verbal and visual methods complement each other to the benefit of planning practice. Combining methods acknowledges recent theoretical conceptualizations of landscape. Abstract: Public participation in landscape planning and management has received increased attention across Europe since the European Landscape Convention (ELC) came into force in 2004. The ELC has now been ratified by many countries, which have been working on its implementation for up to several years. In this article, we study experiences from public participation in five different planning processes in Norway, and we assess the methods used according to a set of evaluation criteria developed in a European context: Scope, Representativeness, Timing, Comfort and Convenience, and Influence. Subsequently we identify ten singular methods as being particularly effective in terms of contributing significantly to increasing scores of Scope, Representativeness, and Comfort and convenience, i.e. the criteria most influenced by the methods chosen. All ten methods identified contribute to increase scores on one or two evaluation criteria, which underlines the importance of combining different methods to achieve effective participation within the restricted framework of a concrete spatial planning process. In an international perspective it seems most fruitful to apply a set of both dominantly verbal methods as practiced in Norway and somewhat more visual approaches used in other countries. This would also acknowledge basic differences among theoretical understandings of landscape and follow a recent scientific development of the concept of landscape.